Effect and mechanism of geological structures on coal seam gas occurrence in Changping minefield. Issue 1 (15th October 2019) - Chen, Xiangjun; Li, Liyang; Yuan, Yu; Li, Hong
Abstract: The main factor affecting the gas content in a coal seam is the geological structure, and different types of geological structure have different effects on the gas content in a coal seam. To explore the main controlling factors of gas content in coal seam No. 3 in the Changping minefield, and the effect of different geological structures on gas control in a coal seam, this study analyzes the types and quantities of geological structures in the Changping minefield. Further, geological boreholes are used to sample and analyze coal seams near different geological structures and at different burial depths. The results show that the main controlling factor of gas content in a coal seam is the burial depth of the coal seam, and the gas content tends to increase with the increasing depth. A geological structure has an effect on the occurrence of coal seam gas in a local area, and the gas content in the coal seam near a fault is 1.6 times that in the normal areas at the same depth. The gas content in the upper wall of a normal fault is 21.6% higher than that in the lower wall. The syncline and anticline axes are prone to form gas accumulation areas, where the gas content is 30%‐60% higher than the normal level. Gas accumulation is prone to occur around a collapse column, and the gas content there is 2.47 times higher than that in a normal area at the same burial depth. Combining the formation mechanism and structural characteristics of different geological structures, this study analyzes the effect of geological structures on coal seam gas quantitatively and provides a theoretical basis for the prevention and control of gas disasters in the Changping minefield. Abstract : This study analyzes the types and quantities of geological structures in the Changping minefield. Further, geological boreholes are used to sample and analyze coal seams near different geological structures and at different burial depths.